Reticular erythematous mucinosis - O. V. Antonova; P. N. Trofimov; I. E. Belousova; A. V. Samtsov (Vestnik Dermatologii i Venerologii, 2017)
This article presents modern data related to the clinical picture, pathologic features and treatment options of reticular erythematous mucinosis (REM). There is an opinion that REM, lupus erythematosus tumidus and Jessner - Kanof lymphocytic infiltration of the skin are similar nosological forms.